Outcomes of IncobotulinumtoxinA Injection on Myalgia and Arthralgia in Patients Undergoing Temporomandibular Joint Arthroscopy: A Randomized Controlled Trial - David Faustino Ângelo; David Sanz; Francesco Maffia; Henrique José Cardoso (Toxins, 2023)
Background: Several studies have considered Botulinum Neurotoxin Type A injections effective in treating temporomandibular joint disorder (TMD) symptoms. A double-blind, randomized, controlled clinical trial investigated the benefit of complementary incobotulinumtoxinA (inco-BoNT/A) injections in the masticatory muscles of patients submitted to bilateral temporomandibular joint (TMJ) arthroscopy. Methods: Fifteen patients with TMD and an indication for bilateral TMJ arthroscopy were randomized into inco-BoNT/A (Xeomin, 100 U) or placebo groups (saline solution). Injections were carried out five days before TMJ arthroscopy. The primary outcome variable was a Visual Analogue Scale for TMJ arthralgia, and secondary outcomes were the myalgia degree, maximum mouth opening, and joint clicks. All outcome variables were assessed preoperatively (T0) and postoperatively (T1—week 5; T2—6-month follow-up). Results: At T1, the outcomes in the inco-BoNT/A group were improved, but not significantly more than in the placebo group. At T2, significant improvements in the TMJ arthralgia and myalgia scores were observed in the inco-BoNT/A group compared to the placebo. A higher number of postoperative reinterventions with further TMJ treatments were observed in the placebo group compared to inco-BoNT/A (63% vs. 14%). Conclusions: In patients submitted to TMJ arthroscopy, statistically significant long-term differences were observed between the placebo and inco-BoNT/A groups.